Stewardship Climate Scale: An Assessment of Reliability and Validity - Neubaum,Donald; Thomas,Christopher H.; Dibrell,Clay; Craig,Justin B. (Family Business Review, 2017)
While stewardship theory is often used to explain family business outcomes, no prior empirical study has used a validated measure of stewardship. We, therefore, surveyed 846 managers and subordinates from 221 family- and non-family firms in the US and Australia to develop a reliable and valid stewardship climate scale. We found family firms have a stronger stewardship climate and the relationship between stewardship climate and performance is mediated by innovativeness, and the effects of stewardship are stronger in family firms, confirming the value of stewardship theory, and our scale, when explaining family business outcomes.
Keywords: Strategy & Entrepreneurship

Linking the formal strategic planning process, planning flexibility, and innovativeness to firm performance - Dibrell,Clay; Craig,Justin; Neubaum,Donald (Journal of Business Research, 2015)
We explore how formal strategic planning processes, adaptive capabilities, and innovativeness are associated with firm financial performance in a multi-industry sample (N = 448). Our results suggest both formal strategic planning processes and adaptive capabilities are positively associated with innovativeness. In addition, we find innovativeness fully mediates the relationships from formal strategic planning and adaptive capabilities to firm financial performance. This implies that organizations that concurrently act and react will be in a more advantageous competitive position than those unable to master this paradoxical conundrum.
Keywords: Management; Strategy & Entrepreneurship

Social Issues in the Family Enterprise - Van Gils,Anita; Dibrell,Clay; Neubaum,Donald; Craig,Justin (Family Business Review, 2014)
Keywords: Management; Strategy & Entrepreneurship

Balancing Natural Environmental Concerns of the Internal and External Stakeholders in Family and Non-family Businesses - Neubaum,Donald; Dibrell,Clay; Craig,Justin (Journal of Family Business Strategy, 2012)
While researches have long suggested that firms must be attentive to their key stakeholders, the question of how attention to different stakeholders may have different benefits for different firms has not been well addressed. This is especially true in the case of family businesses, which confront a unique set of stakeholder challenges, and socioemotional goals not confronted by non-family firms. In this study, we investigate the effect of these competing demands across these different types of firms. We argue that while being attentive to both internal and external stakeholders is important to firm performance in family and non-family firms, family firms can benefit more when they match their concern for natural environmental stakeholders with a demonstration of concern for their employees. By effectively leveraging the power of these critical internal stakeholders, family firms can gain competitive advantages over non-family firms as it is through these internal stakeholders which the demands of external stakeholder are often met.
Keywords: Management; Strategy & Entrepreneurship

A study of Schumpterian (radical) vs. Kirznerian (incremental) innovations in knowledge intensive industries - Dibrell,Clay; Craig,Justin; Cromer,Cory (Journal of Strategic Innovation and Sustainability, 2011)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Untitled - Dibrell,Clay; Neubaum,Donald; Craig,Justin (International Family Enterprise Research Academy (IFERA), 2011)
Keywords: Management; Strategy & Entrepreneurship

Internal Corporate Venturing in Multi-General Family Businesses - Garrett,Robert; Craig,Justin; Zellweger,Thomas; Dibrell,Clay (2010 Western Academy of Management, 2010)
Keywords: Strategy & Entrepreneurship

Overcoming the Liability of Theoretical Newness: The Case for Stewardship Theory - Dibrell,Clay; Craig,Justin; Neubaum,Donald (Babson Kauffman Entrepreneurship Research Conference, 2010)
Keywords: Management; Strategy & Entrepreneurship

Addressing Natural Environmental Concerns from Within: Investigating the Role of Internal Stakeholders in Family and Non-Family Businesses - Neubaum,Donald; Dibrell,Clay; Craig,Justin (Family Enterprise Research Conference, 2009)
Keywords: Management; Strategy & Entrepreneurship

Culture of Family Commitment and Strategic Flexibility: The Moderating Effect of Stewardship - Zahra,Shaker; Hayton,James; Neubaum,Donald; Dibrell,Clay; Craig,Justin (Entrepreneurship, Theory and Practice, 2008)
Keywords: Management; Strategy & Entrepreneurship

Disabled Enterpreneurs: A Model of Entrepreneurial Intention - Baldridge,David; Dibrell,Clay; Neubaum,Donald (Babson Conference, 2008)
Keywords: Management; Strategy & Entrepreneurship

Founding family influence and the moderating effects of product market competition on firm performance: Implications for corporate governance - Randoy,Trond; Dibrell,Clay; Craig,Justin (Small Business Economics, 2008)
Keywords: Management; Strategy & Entrepreneurship

The Impact of Firm Natural Environment Policy on the Market Orientation to Innovation Relationship in SMEs - Dibrell,Clay; Craig,Justin; Hansen,Eric N. (Babson Kauffman Entrepreneurship Research Conference, 2008)
Keywords: Management; Strategy & Entrepreneurship

Leveraging family-based brand identity to enhance firm competitiveness and performance. - Craig,Justin; Dibrell,Clay; Davis,P. S. (Journal of Small Business Management, 2008)
Keywords: Management; Strategy & Entrepreneurship

A Model Of Entrepreneurial Intentions Within The Persons With Disabilities Population - Baldridge,David; Dibrell,Clay; Neubaum,Donald (Frontiers of Entrepreneurship Research, 2008)
While self-employment presents many challenges, an entrepreneurial path for a person with a disability can mean the difference between unemployment or severe underemployment and a truly exceptional and prosperous career. Recent research highlights the importance of entrepreneurial intentions (i.e., the interest of a person in starting, acquiring or buying a business) as a precursor to entrepreneurial behavior (Zhao et al., 2005). Further, entrepreneurial self-efficacy (Zhao et al., 2005), defined as the level of confidence individuals have to identify new opportunities, create products, think creatively, or commercialize an idea, is positively associated with entrepreneurial intention. In reviewing the literature on people with disabilities, however, we find reason to believe that this model does not fully explain the entrepreneurial activities of persons with disabilities. Thus, we integrate the literatures on entrepreneurship and people with disabilities to propose a refined model. A few of the propositions offered by our model are included below.
Keywords: Management; Strategy & Entrepreneurship

A Model Of The Impact Of Disability Attributes On Career Utility And Entrepreneurial Intentions. - Dibrell,Clay; Baldridge,David; Neubaum,Donald (Academy of Management Annual Meeting, 2008)
Keywords: Management; Strategy & Entrepreneurship

Strategic Planning And Flexibility As Governance Control Mechanisms In Family And Non-Family Firms. - Dibrell,Clay; Craig,Justin; Neubaum,Donald (Academy of Management Annual Meeting, 2008)
Keywords: Management; Strategy & Entrepreneurship

Being the boss and working for a boss: Upsides and downsides. - Craig,Justin; Schaper,M.; Dibrell,Clay (The 2007 Australian-New Zealand Academy of Management Conference, 2007)
Keywords: Management; Strategy & Entrepreneurship

Between a strategic rock and a hard place: Planning and flexibility in family and non-family firms. - Dibrell,Clay; Craig,Justin (2007 Australian-New Zealand Academy of Management Conference, 2007)
Keywords: Management; Strategy & Entrepreneurship

Dynamic strategic planning: Achieving strategic flexibility through formalization. - Dibrell,Clay; Down,Jon; Bull,Lyndall (Journal of Business and Management, 2007)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Family Culture and Strategic Flexibility: The Moderating Effects of Stewardship - Neubaum,Donald; Craig,Justin; Dibrell,Clay; Hayton,James; Zahra,Shaker (Family Business Conference, 2007)
Keywords: Management; Strategy & Entrepreneurship

Fueling innovation through information technology in SMEs - Dibrell,Clay; Davis,P. S.; Craig,Justin (Journal of Small Business Management, 2007)
Keywords: Management; Strategy & Entrepreneurship

Integration of value chain position and Porters (1980) competitive strategies in the market orientation conversation: An examination of upstream and downstream activities. - Nicovich,Stefan; Dibrell,Clay; Davis,Peter S (Journal of Business & Economic Studies, 2007)
Keywords: Management; Strategy & Entrepreneurship

Leveraging family-based brand identity to enhance firm competitiveness and performance - Dibrell,Clay; Craig,Justin; Davis,P. S. (The Third Annual Office Depot Small Business Research Forum on “Family Entrepreneurship", 2007)
Keywords: Management; Strategy & Entrepreneurship

Measuring legitimacy of startups: The development of constructs and their parameters. - Johnson,A.; Dibrell,Clay; Holcomb,R.; Craig,Justin (2007 American Agricultural Economics Association Meeting, 2007)
Keywords: Management; Strategy & Entrepreneurship

Navigating the Competitive Landscape: The Mediating Role of Innovation in Strategic Planning Capabilities - Neubaum,Donald; Dibrell,Clay; Craig,Justin (Academy of Management National Meeting, 2007)
Keywords: Management; Strategy & Entrepreneurship

Overcoming liability of newness through legitimacy: A stakeholder salience perspective - Dibrell,Clay; Johnson,A.; Craig,Justin; Moores,K. J. (2007 Australian-New Zealand Academy of Management Conference, 2007)
Keywords: Management; Strategy & Entrepreneurship

The Road to Legitimacy: A Study of Startups and their Established Competitors in the Australian Wine Industry - Dibrell,Clay; Johnson,Aaron; Davis,Peter S; Moores,Ken; Craig,Justin (Babson Kauffman Entrepreneurship Research Conference, 2007)
Keywords: Management; Strategy & Entrepreneurship

Market orientation, strategy, and performance in the forest industr - Hansen,Eric; Dibrell,Clay; Down,Jon (Forest Science, 2006)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Performance implications of temporal orientation and IT in organization-environment alignment - Dibrell,Clay; Davis,Peter S (Academy of Management, 2006)
Keywords: Management; Strategy & Entrepreneurship

Chronicity and innovation as responses to environmental disruptions - Dibrell,Clay; Davis,P. S.; Carol,T. (Academy of Management Conference, 2005)
Keywords: Management; Strategy & Entrepreneurship

The evolving role of cooperation among multinational corporations and indigenous organizations in transition economies: A migration away from confrontation - Danskin,P.; Dibrell,Clay; Kedia,B. L. (Journal of World Business, 2005)
Recent trends toward greater globalization and the increasing number of transition economies are changing the nature of the relationships among multinational enterprises (MNEs), organizations in transition economies (OTEs), and the OTEs' governments from a traditional conflict-based perspective towards consisting of cooperation and collaboration. This paper draws on the theory of cooperation that incorporates the concepts of substitutability (substitution of goals), cathexis (commitment to a specific goal), and inducibility (open to influence) to describe the emerging interactive relationship between MNEs and OTEs. Due to changing global competitive trends, we propose that MNEs, OTEs, and transition economy governments act in their best interests through a continuum of cooperation and confrontation. We propose that the two theories of cooperation and confrontation are not paradoxical but are in effect complementary.
Keywords: Management; Strategy & Entrepreneurship

The influence of internationalization on time-based competition - Dibrell,Clay; Davis,P. S.; Danskin,P. (Management International Review, 2005)
Keywords: Management; Strategy & Entrepreneurship

Innovation and Firm Performance: The Role of Information Technology in Small and Medium-Sized Firms - Craig,Justin; Dibrell,Clay; Davis,P. S. (Strategic Management Society Conference, 2005)
Keywords: Management; Strategy & Entrepreneurship

Empirical evaluation of an integrated supply chain model for small and medium sized firms - Sakaguchi,T.; Nicovich,S.; Dibrell,Clay (Information Resources Management Journal, 2004)
With increased global competitive pressures, companies operating in these competitive environments are not only looking to their distribution division to save money, but also to generate competitive advantages. One technique is the integrated supply chain. However, this process has not met with success for all companies, leading some managers to consider the appropriateness of an integrated supply chain. This dearth of success could be attributed to the lack of scholarship to guide managers in their efforts to formulate and then implement their integrated supply chain strategies. In an effort to fill this gap, our paper draws on resource dependency theory and the realities of ever-increasing information technology sophistication as enablers of successful supply chain integration, resulting in the creation of our model to guide managers throughout this process. Through a Web-based survey, 329 responses were collected and analyzed through a structural equation modeling technique using LISREL to confirm the relationships in the model.
Keywords: Management; Strategy & Entrepreneurship

Entrepreneurial firm success: A triadic examination of strategy planning, choice and flexibility - Down,Jon; Dibrell,Clay; Craig,Justin (Babson Kauffman Entrepreneurship Research Conference, 2004)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Founding family leadership, product market competition, and firm performance among publicly traded firms - Dibrell,Clay; Randøy,T. (Financial Management Association European Conference, 2004)
Keywords: Management; Strategy & Entrepreneurship

Gaining and Sustaining Competitive Advantage: The Effects of Strategic Flexibility and Information Technology Among Internationalizing Firms - Dibrell,Clay; Babakus,E.; Davis,P. S. (Academy of International Business Conference, 2004)
Keywords: Management; Strategy & Entrepreneurship

Integrating firm temporal activities with information technology: Innovation and performance implications - Dibrell,Clay (Strategic Management Society Conference, 2004)
Keywords: Management; Strategy & Entrepreneurship

Market orientation: The role of strategic planning and strategy choice on firm performance - Dibrell,Clay; Hansen,E.; Down,Jon (Academy of Management Conference, 2004)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

The moderating role of strategic flexibility in the strategic planning to innovation relationship: A study of entrepreneurial firms. - Craig,Justin; Dibrell,Clay; Down,Jon (Babson Kauffman Entrepreneurship Research Conference, 2004)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Applying methodological perspecitives to Stategic Management - Dibrell,Clay (Transforming Leadership Professional Development Workshop at the Academy of Management Annual Meeting, 2003)
Keywords: Management; Strategy & Entrepreneurship

Consumers and technology: Are we creating relationships or distance? - Peterson,R. L.; Dibrell,Clay (Academy of Entrepreneurship Journal, 2003)
Keywords: Management; Strategy & Entrepreneurship

The effects of IT in the value cycleperformance linkage - Dibrell,Clay; Davis,P. S. (Strategic Management Society Conference, 2003)
Keywords: Management; Strategy & Entrepreneurship

An Examination of Time Pacing, Strategy, and Performance in Born Global Firms - Dibrell,Clay; Harveston,P.; Davis,P. S. (Babson College Kauffman Foundation Entrepreneurship Research Conference, 2003)
Keywords: Management; Strategy & Entrepreneurship

Inhibitors and enhancers: The role of internal and external stakeholders in the transition process - Kedia,B. L.; Dibrell,Clay; Harveston,P. D. (Journal of International Business and Economy, 2003)
Keywords: Management; Strategy & Entrepreneurship

A resource-based view and market orientation theory examination of the role of "familiness" in family business success - Dibrell,Clay; Down,Jon; Green,Mark; Hansen,E.; Johnson,A. (Family Business Network Academic Research Forum, 2003)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Strategic Planning Flexibility and Firm Performance Under Distinct Competitive Strategy Choices - Dibrell,Clay; Down,Jon (Academy of Management Conference, 2003)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Strategic Planning Lessons from Successful Vertically Integrated Food Processors - Dibrell,Clay; Johnson,A. (Proceedings of the Annual Conference of the Food Distribution Research Society, 2003)
Keywords: Management; Strategy & Entrepreneurship

Strategy process insights: Achieving planning discipline and strategic flexibility - Down,Jon; Dibrell,Clay (Strategic Management Society Conference on Strategic Process., 2003)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Strengthening the strategic flexibility-performance relationship: The role of IT among internationalizing firms - Dibrell,Clay; Davis,P. S. (Strategic Management Society Conference, 2003)
Keywords: Management; Strategy & Entrepreneurship

Time-based strategies and firm performance - Dibrell,Clay; Davis,P. S. (Academy of Management Conference, 2003)
Keywords: Management; Strategy & Entrepreneurship

Adequate measurement isn't just "nice:" A review of measurement practices in management research - Dibrell,Clay; Cogliser,C.; Hua,S. (Academy of Management Annual Meeting, 2002)
Keywords: Management; Strategy & Entrepreneurship

Competitive Strategy, IT Asset Investment and Firm Performance: Implications for Born Global Firms - Dibrell,Clay; Harveston,P. D.; Davis,P. S. (Babson Kauffman Entrepreneurship Research Conference, 2002)
Keywords: Management; Strategy & Entrepreneurship

Development of an integrated supply chain model - Dibrell,Clay; Sakaguchi,T.; Nicovich,S. (Americas Conference on Information Systems, 2002)
Keywords: Management; Strategy & Entrepreneurship

How and why Norwegian MNCs commit resources abroad: Beyond choice of entry mode - Randøy,T.; Dibrell,Clay (Management International Review, 2002)
This study provides a model of MNC's commitment of resources in foreign countries. The results suggest that the strategic motives are important to MNC's decisions. * The data is based on Norwegian MNC's activities in Sweden, Germany, the United Kingdom, Spain, Poland, Japan, and the United States. Key Results * This research reveals how and why firm-specific, location-specific, and transaction-specific variables need to be supplemented by strategic factors to fully understand MNC's resource commitments abroad.
Keywords: Management; Strategy & Entrepreneurship

The impact of time on the strategy-performance relationship: Implications for managers - Davis ,P. S.; Dibrell,Clay; Janz ,B. (Industrial Marketing Management, 2002)
Keywords: Management; Strategy & Entrepreneurship

The influence of internationalization on time-based competition - Dibrell,Clay; Davis,P. S.; Harveston,P. D. (Academy of Management Annual Meeting, 2002)
Keywords: Management; Strategy & Entrepreneurship

Leadership, competitive environments and firm performance in closely held firms - Dibrell,Clay; Randøy,T.; Davis,P. S. (Strategic Management Society Conference, 2002)
Keywords: Management; Strategy & Entrepreneurship

Long- vs. short-term performance perspectives of Western European, Japanese, and U.S. countries: where do they lie? - Peterson ,R. L.; Dibrell,Clay; Pett,T. L. (Journal of World Business, 2002)
This paper examines the differences between Eastern and Western companies regarding long- vs. short-term orientations. Utilizing Hofstede's long-term orientation index, this study scrutinizes both long- and short-term performance measurements for companies from Western Europe, Japan, and the United States. The findings suggest that Western European companies place an equally higher priority on both long- and short-term measures of performance compared to companies from Japan and the United States. Additionally, Japanese companies were postulated by the literature to employ a long-term orientation toward company performance greater than U.S. companies. However, our results do not support this statement, as U.S. and Japanese companies were not statistically significantly different.
Keywords: Management; Strategy & Entrepreneurship

Organization design: The continuing influence of information technology - Dibrell,Clay; Miller,T. (Management Decision, 2002)
Drawing from an information processing perspective, this paper examines how information technology (IT) has been a catalyst in the development of new forms of organizational structures. The article draws a historical linkage between the relative stability of an organization's task environment starting after the Second World War to the present environmental instability that now characterizes many industries. Specifically, the authors suggest that advances in IT have enabled managers to adapt existing forms and create new models for organizational design that better fit requirements of an unstable environment. Time has seemingly borne out this hypothesis as the bureaucratic structure evolved to the matrix to the network and now to the emerging shadow structure. IT has gone from a support mechanism to a substitute for organizational structures in the form of the shadow structure. The article suggests that the evolving and expanding role of IT will continue for organizations that face unstable environments.
Keywords: Management; Strategy & Entrepreneurship

Revisiting the complex relationship between multinational enterprises and organizations in transitions economies through the logic of the Copenhagen Interpretation - Dibrell,Clay; Harveston ,P. D.; Kedia,B. L. (Academy of International Business Annual Meeting, 2002)
Keywords: Management; Strategy & Entrepreneurship

The second coming of deliberate strategic planning processes: Insights gained from a global industry - Down,Jon; Dibrell,Clay (Western Academy of Management Annual Meeting, 2002)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Strategic thinking in a global industry: Strategy process insights from forest products firms - Dibrell,Clay; Down,Jon (Strategic Management Society Conference, 2002)
Keywords: Entrepreneurship; Management; Strategy & Entrepreneurship

Global integrated supply chain: A theoretical typology - Dibrell,Clay; Nicovich,Stefan; Sakaguchi,T. (Global Information Technology Management (GITM) World Conference, 2001)
Keywords: Management; Strategy & Entrepreneurship

The influence of firm internationalization and cycle time on firm performance - Dibrell,Clay; Harveston,P. D.; Davis,P. S. (Academy of International Business Annual Meeting, 2001)
Keywords: Management; Strategy & Entrepreneurship

A longitudinal analysis of country of origin as a predictor of strategic change and performance in global industries - Dibrell,Clay; Davis,P. S.; Pett,T. L. (Academy of Management Annual Meeting, 2001)
Keywords: Management; Strategy & Entrepreneurship

A process model of global strategic alliance formation - Pett,T. L.; Dibrell,Clay (Business Process Management Journal, 2001)
Develops a conceptual framework of global strategic alliances by using the hybrid type of organization as part of the framework. The framework illustrates the relationships of various characteristics that might be present in an industry and across national boundaries that would influence alliance participation. The model developed here is based on four echelons, the exploratory, recurrent, relational, and outcome stages. Concludes with some general comments on the proposed global strategic alliance framework.
Keywords: Management; Strategy & Entrepreneurship

Time pacing behaviors and performance: A three-study exploration - Dibrell,Clay; Davis,P. S. (Strategic Management Society Conference, 2001)
Keywords: Management; Strategy & Entrepreneurship

A longitudinal analysis of the effects of information technology on firm performance in a global industry - Dibrell,Clay; Davis,P. S.; Pett,T. L. (Academy of International Business Annual Meeting, 2000)
Keywords: Management; Strategy & Entrepreneurship

The strategy-performance relationship: Time the complementary dimension - Dibrell,Clay; Davis,P. S.; Janz,B. (Academy of Management Meetings, 2000)
Keywords: Management; Strategy & Entrepreneurship